The Proto-Oncogene TWIST1 Is Regulated by MicroRNAs - Nairismägi, Maarja-Liisa (Public Library of Science, 2013)
Upregulation of the proto-oncogene Twist1 is highly correlated with acquired drug resistance and poor prognosis in human cancers. Altered expression of this multifunctional transcription factor is also associated with inherited skeletal malformations. The mammalian Twist1 3′UTRs are highly conserved and contain a number of potential regulatory elements including miRNA target sites. We analyzed the translational regulation of TWIST1 using luciferase reporter assays in a variety of cell lines. Among several miRNAs tested, miR-145a-5p, miR-151-5p and a combination of miR-145a-5p + miR-151-5p and miR-151-5p + miR-337-3p were able to significantly repress Twist1 translation. This phenomena was confirmed with both exogenous and endogenous miRNAs and was dependent on the presence of the predicted target sites in the 3′UTR. Furthermore, the repression was sensitive to LNA-modified miRNA antagonists and resulted in decreased migratory potential of murine embryonic fibroblast cells. Understanding the in vivo mechanisms of this oncogene's regulation might open up a possibility for therapeutic interference by gene specific cancer therapies.